The Interpretation of Qalam in the Quran as a Foundation of Scientific and Technological Progress - Satria Tenun Syahputra; Ahmad Murtaza MZ (Dialogia, 2022)
The word of qalam in the Quran is mentioned very limited, it is only mentioned four times. In everyday life, the word of qalam is known as a pen or a writing tools, even though if the word is analyzed even further will not have as simple meaning as that. This research tend to analyze the word of qalam in the Quran comprehensively by finding out the signs of the words in some verses of the Quran with semiotics approachment. In this case, the author will utilize the semiotic theory of Ferdinad D Saussure that is binary opposition consist of signifier–signified, langue–parole, syncronic–dyacronic and syntagmatic–paradygmatic to reveal the meaning of the word of qalam in the Quran as a sign. This research is a library research with a qualitative content analysis that analyze a message of a media as an object of the research. The result of the analysis declare that the word of qalam is not only a pen or a writing tools by meaning, but also a pen use by the angels to write down the destiny, a pen of the knowledge or the tools of knowledge including the modern tools, the pen as a comparison of the ability of human beings and the mighty of God, and a pen as a media of lottery or as arrows. This kind of research must be developed recently to prove that the Quran is in line with the development of times, sciences and civilization.